A Comparative Study Between Team Games Tournament And Student Teams Achievement Divisions In Teaching Reading - Aulia Dzaky Valid; Muhammad Asrori; kristiandi kristiandi (Universitas Sebelas Maret, 2020)
This study aims at finding out whether there is a significant difference in reading comprehension between students taught using Team Games Tournament (TGT) and students taught using Student Teams Achievement Divisions (STAD); and which method has a better result in teaching reading between TGT and STAD. The research method used in this study is the quasi-experimental research design. This research was conducted at one of junior high school in Purwodadi. The population of the research was the eighth grade students in that school. The samples were students of class VIII A as the experimental group which consisted of 32 students and students of class VIII D as the control group which consisted of 32 students. The research instruments used to collect the data in this study were tests, including pre-test and post-test. The data were analysed by using the t-test formula and the score improvement to determine the significant difference and the better method respectively. The data computation using the t-test shows that t observation (to) (3.11) was higher than t table (tt) (1.96). The post-test score shows that the mean score of the experimental group is 80.625, while the mean score of the control group is 74.625. It means that the mean score of the experimental group is higher than the mean score of the control group. In a nutshell, there is a significant difference in reading comprehension between the students taught using STAD and the students taught using TGT and TGT is better than STAD to teach reading.